Ask the right question: a critical step for practicing evidence-based laboratory medicine*. (July 2013) - Price, Christopher P; Christenson, Robert H
The purpose of laboratory medicine is to facilitate better decision making in clinical practice and healthcare delivery. Decision making implies an unresolved issue, problem or unmet need. The most important criterion for any investigation to be of value in clinical practice is that it addresses an unmet need. The different ways in which laboratory investigations are utilized in patient care can be represented in the form of questions. It is important that these questions are articulated to highlight the variables that will impact on the effectiveness of the investigation in the scenario being considered. These variables include the characteristics of the patient (or population) and clinical setting, the nature of the decision and action taken on receipt of the test result and the expected outcome. Asking a question is the first step of the evidence-based laboratory medicine (EBLM) cycle, the other steps being acquiring the evidence, critically appraising the evidence, applying the evidence and auditing use of the evidence. Getting the question right determines the quality of the whole process, thus, defines the quality in practice of laboratory medicine. Whilst the main focus of the EBLM cycle is to provide a strong evidence base for use in clinical practice, it is clear that the five steps are equally applicable in commissioning, delivery and audit (performance management) of services. Asking the right question is crucial to improving the quality of evidence, and practice, in laboratory medicine, and should be used in routine laboratory medicine practice and management throughout healthcare.